Current and Future Therapeutic Targets: A Review on Treating Head and Neck Squamous Cell Carcinoma - Madhukar, Geet; Subbarao, Naidu (Current Cancer Drug Targets, 2021)
Head and neck squamous cell carcinoma (HNSCC) continues to be a global public health burden even after a tremendous development in its treatment. It is a heterogeneous cancer of upper aero-digestive tract. The contemporary strategy to treat cancer is the use of anticancer drugs against proteins possessing abnormal expression. Targeted chemotherapy was found successful in HNSCC, but, there is still a stagnant improvement in the survival rates and high recurrence rates due to undesirable chemotherapy reactions, non-specificity of drugs, resistance against drugs and drug toxicity on non-cancerous tissues and cells. Various extensive studies lead to the identification of drug targets capable to treat HNSCC effectively. The current review article gives an insight into these promising anticancer targets along with knowledge of drugs under various phases of development. In addition, new potential targets that are not yet explored against HNSCC are also described. We believe that exploring and developing drugs against these targets might prove beneficial in treating HNSCC.
Keywords: HNSCC